Influence of Gd doping on morphological, toxicity and magnetic properties of ZnO nanorods. (September 2021) - Satpathy, S.K.; Panigrahi, U.K.; Panda, S.K.; Thiruvengadam, V.; Biswal, R.; Luyten, W.; Mallick, P.
Abstract: Properties of chemically synthesized Zn1−x Gdx O (x = 0.01, 0.03 and 0.05) nanorods were explored through microstructural, morphological, toxicity and magnetic characterizations. Hexagonal wurtzite structure of all the samples without any impurity phases was confirmed by X-ray diffraction characterization. The micrographs of transmission electron microscope and field emission scanning electron microscope revealed the rod shape morphology of the samples. A systematic evolution of room temperature ferromagnetism of ZnO nanorods with increasing Gd doping content was observed. Gd doped ZnO nanorods showed narrow-spectrum antibacterial activity against the most opportunistic Gram-positive pathogen bacterium, S. aureus as compared to commercial ZnO. From cytotoxicity assessment with Caenorhabditis elegans and Danio rerio, the samples were non-toxic or showed little toxicity at the highest concentration tested (100 µg/mL) except for 1% Gd doped ZnO. Our study demonstrates the possible usefulness of the materials in spintronic, magnetic media device as well as bio-medical applications. Highlights: Hexagonal wurtzite structure of ZnO is not affected by Gd doping. Ferromagnetic property of ZnO nanorods are enhanced with Gd doping. All the samples showed antimicrobial effects against S. aureus. The samples could be beneficial for optoelectronics, spintronics as well as for bio-medical applications.